Biodiesel production using co-solvents: a review (Research, Society and Development, 2020)
Biodiesel is a renewable and biodegradable biofuel, generally produced by the fatty materials transesterification. Due to its importance in the diversification of the energy matrix of countries, various studies have been carried out to improve its production process. One of the technologies developed is the use of co-solvents in the process. The co-solvents decrease the mass transfer resistance between the oil and the alcohol during the chemical reaction. In this paper, a review of the literature on the biodiesel production using co-solvents was presented. The research gathered information about various studies that are relevant to the theme, aiming to show the state of the art, the substances most used as co-solvents, and the conditions of the process variables that result in high yields of fatty acid methyl esters (FAME). In the homogeneous basic catalysis of vegetable oils, potassium hydroxide is the most used catalyst. Its range of application normally varies from 0.5% to 1.8% in relation to the mass of oil. The reaction time may vary from 10 minutes to 2 hours, the temperature from 25 °C to 100 °C, the molar ratio (MR), from 3:1 to 12:1, and the amount of 30% (w/w) co-solvent, or in some cases up to 0.7:1 co-solvent to alcohol molar ratio.